Risk factors of developmental delay: a community-based study - Mei Neni Sitaresmi; Djauhar Ismail; Abdul Wahab (Paediatrica Indonesiana, 2008)
Background Developmental delay is a common problem inchildren. Early detection of this disorders is mandatory in orderto provide early interventions. Identification of the risk factors isimportant for strategic intervention.Objective To identify risk factors of developmental delay inchildren under five years old.Metlwds A community-based study of developmental screeningwas conducted, in Bambanglipuro, Bantul district, Province ofYogyakarta, between September and October 2007. Developmentalscreening was performed using a Kuesioner Pra Skrining Perkembangan(KPSP).Results Out of 632 children aged 3 to 60 months, 407 (64%) hadnormal development, 81 (28%) doubtful and 43 (8%) suspecteddevelopmental delay. A number of factors identified as the riskof suspected developmental delay were undernourished (OR 2.3,95%CI 1.1 ; 4.8) , low birth weight (OR 2.6, 95%CI 1.1 ; 6.1), loweducational level of mother (O R 2.5, 95%CI 1.3; 4.9) , workingmother (O R 1.8, 95%CI 1; 3.5), and poor socio-economic status(SES) families (OR 2.7, 95%CI 1.3; 5.4). Multivariate logisticregression analysis showed that poor SES was the strongest riskfactor of suspected developmental delay (adjusted OR 2.8, 95%CI1.4;5.7) .Conclusions Poverty, low maternal educational level andintrauterine malnutrition during as well as malnutrition duringinfant period are risk factors of developmental delay. Integratedstrategies should be conducted to solve the problems to preventmore children suferred from developmental delay.